A Gameplay Definition through Videogame Classification. (22nd April 2008) - Djaouti, Damien; Alvarez, Julian; Jessel, Jean-Pierre; Methel, Gilles; Molinier, Pierre
Abstract : This paper is part of an experimental approach aimed to raise a videogames classification. Being inspired by the methodology that Propp used for the classification of Russian fairy tales, we have identified recurrent diagrams within rules of videogames, that we called "Gameplay Bricks". The combinations of these different bricks should allow us to represent a classification of all videogames in accordance with their rules. In this article, we will study the nature of these bricks, especially the link they seem to have with two types of game rules: the rules that allow the player to "manipulate" the elements of the game, and the rules defining the "goal" of the game. This study will lead to an hypothesis about the nature of gameplay.